Tradisi dalam Budaya Jepang pada Anime Konohana Kitan Karya Sakuya Amano: Kajian Folklor Sebagian Lisan - Ulah, Rif'ah Fatkhul; Suryawati, Cicilia Tantri (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2024)
Japanese culture is rich of traditions and festival that have become an inseparable part of the national identity. One form of these cultural richnesses is matsuri. Matsuri is a festival that honors local gods or celebrates important events in the history of a community in Japan. This tradition continues to live and is passed down from generation to generation, encompassing various aspects such as beliefs, customs and art. This study focuses on the representation of traditional Japanese culture in the anime Konohana Kitan by Sakuya Amano, which represents various elements of Partly Verbal Folklore. Through qualitative analysis, the study analyzes several Japanese cultural traditions such as hanami, kagura dance, Shichi-Go-San, Bon Odori, and religious elements such as Buddhism and Shintoism. This anime does not only serve as a medium of entertainment, but also as an effective educational tool to introduce and preserve Japanese cultural heritage. The results of this study indicate that Konohana Kitan contains many aspects of Partly Verbal Folklore that are still relevant and valued in modern Japanese society, thus making a significant contribution to the preservation and dissemination of traditional Japanese culture. Keywords: anime; partly verbal folklore; tradition.